2012
DOI: 10.1007/s11357-011-9378-2
|View full text |Cite
|
Sign up to set email alerts
|

Survivin expression increases during aging and enhances the resistance of aged human fibroblasts to genotoxic stress

Abstract: Survivin, an important anti-apoptotic protein, is highly expressed in most cancers, which generally arise in cells of older individuals. We have shown here accumulation of survivin and phospho-survivin in aged normal human skin fibroblasts and mice organs. This age-related accumulation of survivin was due to protein stabilization through association with the molecular chaperone Hsp90 protein, which was also up-regulated during aging. Interestingly, Hsp90 binds preferentially to phospho-survivin, which explains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Our studies implicate apoptosis resistance as a key mechanism by which myofibroblast senescence contributes to persistent fibrosis in aging. Indeed, studies in our laboratory and others support the acquisition of an apoptosis-resistant phenotype in senescent fibroblasts, in part related to higher expression of Bcl-2 (36,37). Our current findings of high expression of Bcl-2 in fibroblasts isolated from aged mice subjected to bleomycin injury are consistent with this as one mechanism of apoptosis resistance.…”
Section: Mechanism (16 35supporting
confidence: 87%
“…Our studies implicate apoptosis resistance as a key mechanism by which myofibroblast senescence contributes to persistent fibrosis in aging. Indeed, studies in our laboratory and others support the acquisition of an apoptosis-resistant phenotype in senescent fibroblasts, in part related to higher expression of Bcl-2 (36,37). Our current findings of high expression of Bcl-2 in fibroblasts isolated from aged mice subjected to bleomycin injury are consistent with this as one mechanism of apoptosis resistance.…”
Section: Mechanism (16 35supporting
confidence: 87%
“…Interestingly, Survivin siRNA had not yet been screened to develop senolytic molecules [ 44 46 ]. However, Al-Khalaf et al reported that its inhibition with flavopiridol or specific shRNAs increases the apoptotic response of senescent fibroblast to various stressors [ 48 ]. As a result, sHUVECs are more resistant to apoptosis despite i) Bcl-2 downregulation and ii) exhibition of several characteristics of dysfunctional cells in which the early stages of programmed cell death have been activated, like ROS production, a significant increase in mPTP opening, and slight casp-3 activity, all findings that may be the result of Bcl-2 downregulation.…”
Section: Discussionmentioning
confidence: 99%
“…Al-Khalaf et al found that survivin and phospho-survivin were accumulated in aged normal human skin fibroblasts and mice organs, which may be attributable to HSP90-mediated stabilization of survivin. Inhibition of survivin by flavopiridol or shRNAs increased the apoptotic response of old fibroblasts to various genotoxic agents by restoring the pro-apoptotic Bax/Bcl-2 ratio and increasing the levels of cleaved caspase-3 and PARP ( Al-Khalaf and Aboussekhra, 2013 ). Another study indicated that nuclear accumulation of Yes-associated protein (YAP) could promote the survival of senescent tumor cells by increasing the expression of survivin ( Ma et al, 2016 ).…”
Section: Apoptotic Resistance and The Underlying Mechanism In Sncsmentioning
confidence: 99%